Graduating nurses' self-efficacy in palliative care practice: An exploratory study. (April 2016) - Henderson, Amanda; Rowe, Jennifer; Watson, Karen; Hitchen-Holmes, Deborah
Abstract: Background: Educational institutions and the health care industry agree that graduates from professional programs need to be "work ready" and capable of delivering competent and confident nursing care. One measure of program success is the student's self-efficacy in meeting expected graduate capabilities. In this study student's self-efficacy is related to palliative care graduate capabilities. Aim: To explore graduating Bachelor of Nursing Science (BNSc) students' self-efficacy in caring for palliative care patients. Design: A qualitative design using semi-structured face-to-face interviews. Setting: A regional Australian university. Participants: A purposive sample of 10 students in their final semester of study in a Bachelor of Nursing Science degree program. Method: Semi-structured face-to-face interviews were conducted. Interview questions were informed by published palliative care graduate capabilities. Interview data were transcribed verbatim and coded by capability. The coded data were then analysed to determine evidence of self-efficacy in caring for palliative care patients. Results: All participants had experiences in caring for palliative care patients. However, the responses did not consistently reflect high degrees of self-efficacy in four documented palliative care graduate capabilities required to care for persons with a life-limiting illness. Conclusions: The findings support others that have identified gaps between curriculum and health care industry requirements in terms of students' beliefs about their empowerment to deliver nursing care as graduates. Education interventions and approaches to program evaluation require further development to better support students' growth of self-efficacy in undertaking their graduate roles. Highlights: We examined graduating nursing students' self-efficacy to deliver palliative care. We found that graduating nursing students may not be fully prepared for palliative care practice.